Has the matching between urban population aging and older adult care facilities achieved coupling coordination?—An empirical analysis based on spatiotemporal evolution and multifactor interaction mechanisms - Liu, Q.; Zhao, S. L.; Li, Y. F. (Frontiers in Public Health, 2025)
The aging population has become a global socio-economic challenge, particularly in economically underdeveloped regions, where it profoundly impacts the allocation of medical resources, social security systems, and land use patterns. However, existing research has paid insufficient attention to the coordination between population aging and the spatial distribution of older adult care facilities, making it difficult to provide scientific evidence for optimizing regional older adult care resources. This study explores the temporal and spatial evolution characteristics of aging and its relationship with older adult care facilities based on data from Gansu Province from 2000 to 2020. Using ArcGIS for spatial visualization analysis, we measure matching equity through the Gini coefficient and assess the coupling coordination relationship using a coupling coordination degree model. Additionally, we employ geographic detectors to identify key influencing factors. The findings indicate that the level of aging in Gansu Province continues to rise with significant spatial heterogeneity; northern and central regions experience accelerated aging, while southern areas show slower growth rates. The distribution of older adult care facilities is highly uneven; economically developed cities like Lanzhou concentrate resources, while severely underdeveloped areas in the north and west lack adequate facilities. Fluctuations in the Gini coefficient suggest that equity in matching between aging populations and older adult care facilities has not consistently improved over time; overall coupling coordination levels remain low. Geographic detection results reveal that population density, economic development, fiscal investment, and digital financial development are critical factors affecting matching degrees among these elements. Notably, interaction effects between population density and foundational aspects of aging are most pronounced (q = 0.7498). This study deepens our understanding of the relationship between population aging and older adult care facility matching dynamics while providing a scientific basis for optimizing layout strategies for eldercare infrastructure and land use planning in underdeveloped regions. It emphasizes the necessity of tailored approaches to enhance equity in eldercare resource allocation according to local conditions.